2022
DOI: 10.1016/j.aace.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Bone Disease of the Thoracic Cage: Challenges in the Management of a Rare Entity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“… 7 Another case of Camurati-Engelmann disease reports on the potential development of pituitary insufficiency when the skull base is involved with the disease process. 8 Authors also reported an interesting case of “vanishing bone disease” in a 22-year-old man, 9 and another case of ectopic ACTH secretion due to Ewing sarcoma in a 9-year-old girl is reported. 10 …”
mentioning
confidence: 98%
“… 7 Another case of Camurati-Engelmann disease reports on the potential development of pituitary insufficiency when the skull base is involved with the disease process. 8 Authors also reported an interesting case of “vanishing bone disease” in a 22-year-old man, 9 and another case of ectopic ACTH secretion due to Ewing sarcoma in a 9-year-old girl is reported. 10 …”
mentioning
confidence: 98%